Effects of Ulmi Pumilae Cortex on AGS Gastric Cancer Cells - Lim Bora; Lee Hee Jung; Kim Min Chul; Kim Byung Joo (Korean Pharmacopuncture Institute, 2013)
Objective: Ulmi Pumilae Cortex (UPC) is a deciduous tree with uneven pinnate leaves and is classified as a subfamily of Ulmuceae and contains many pharmacologically active constituents. The aim of this study was to investigate the effects of UPC on the growth and survival of AGS cells, the most common human gastric adenocarcinoma cell lines. Methods: The AGS cells were treated with varying concentrations of UPC. Analyses of the sub G1, caspase-3 activity, and mitochondrial depolarization were conducted to determine whether AGS cell death occured by apoptosis. Furthermore, to identify the role of the transient receptor potential melastatin (TRPM) 7 channels in AGS cell growth and survival, we used human embryonic kidney (HEK) 293 cells overexpressed with TRPM7 channels. Results: The addition of UPC to a culture medium inhibited AGS cell growth and survival. Experimental results showed that the sub G1, caspase-3 activity, and mitochondrial depolarization were increased. Furthermore, TRPM7 channel overexpression in HEK 293 cells exacerbated UPC-induced cell death. Conclusion: These findings indicate that UPC inhibits the growth and survival of gastric cancer cells due to a blockade of the TRPM7 channel activity. Therefore, UPC is a potential drug for treatment of gastric cancer, and TRPM7 channels may play an important role in survival in cases of gastric cancer.